Hubungan antara Parent Attachment dengan Self-Esteem pada Siswa di SMK Negeri 3 Kupang - Natalia Florentina Bengan Ola; Muhammad Dae Pua Upa; Weni Puspita Sari (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
Parent attachment is an important aspect of adolescent development that reflects the extent to which individuals feel emotionally attached to their parents. Self-esteem describes an individual's assessment of himself, including confidence and the ability to face challenges. This research is motivated by the importance of the role of parents in forming emotional attachment that affects the self-esteem of adolescents, especially students of SMK Negeri 3 Kupang. The purpose of the study is to find out the picture of parent attachment and self-esteem of students, as well as the relationship between the two. The approach used is quantitative with a correlational method. The sample consisted of 96 students in grades X and XI (Hospitality, Fashion, Culinary, Hospitality, and TJKT) from various majors, selected through proportional stratified random sampling technique. The instrument was in the form of a Likert scale questionnaire: 26 items to measure parent attachment and 31 items to self-esteem. Data were analyzed using descriptive statistics and Pearson correlation test through SPSS version 22. The results showed that 47.90% of students had high parental attachment, especially in terms of communication and trust, although some still experienced estrangement. As many as 44.80% of students have high self-esteem, seen from the aspects of power, significance, virtue, and competence. The Pearson correlation test yielded a value of r = 0.444 which showed a positive and significant relationship between parent attachment and self-esteem. In conclusion, the stronger the student's attachment to their parents, the higher their self-esteem. Therefore, emotional support and good communication from parents are essential. Schools and families are advised to work together to strengthen this relationship to support students' psychological development.